Antibacterial Potential of Methanol Extract of Red Guava Leaves (Psidium guajava L.) Against Salmonella typhi - Gabriella Marchelita Ginting; Ira Gracela; Meldawati; Adek Amansyah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Typhoid fever is a fever caused by an infection of the gastrointestinal tract, where the infection is caused by the bacterium Salmonella typhi. This infection is generally found in environmental conditions with dense populations and poor hygiene levels. Various plants have been used from generation to generation to treat typhoid fever, one of which is red guava leaves. This study aims to further explore the potential of methanol extract of red guava leaves (Psidium guajava L.) on the activity of Salmonella thyphi in vitro. Methods: This study is an in vitro experimental study using Salmonella thyphi culture. The phytochemical screening test was carried out on the methanol extract of red guava leaves. Furthermore, an assessment of the diameter of the inhibition zone between groups was carried out. Univariate and bivariate analyzes were performed to compare between groups. Results: There was an increase in the diameter of the inhibition zone along with an increase in the dose of methanol extract from red guava leaves. A dose of 100 mg/mL of red guava leaf extract showed a maximum inhibition diameter of 11.85 cm. Conclusion: Methanol extract of red guava leaves (Psidium guajava L.) has the antibacterial activity of Salmonella thyphi along with increasing concentrations.